2021
DOI: 10.1177/1464420721994269
|View full text |Cite
|
Sign up to set email alerts
|

Development of a fuzzy-TOPSIS multi-criteria decision-making model for material selection with the integration of safety, health and environment risk assessment

Abstract: This study presents the development of a fuzzy-TOPSIS multi-criteria decision-making (MCDM) model for material selection with integrated safety, health, and environment risk assessment. As safety, health, and environment is very much linked to sustainable design and manufacturing, it is imperative that safety, health, and environment is taken into consideration in ensuring a comprehensive and holistic material selection process. This paper shows the possibility of fuzzy logic utilization in assessing safety, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2121
2121

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…The variables of the suggested models indicated that at the maximum and minimum levels of health risk, compared with the average levels, the "safety efficiency" was more significant on "safety view". The results confirmed the acceptability of the suggested and tested model [28].…”
Section: Selection Of the Right Modelsupporting
confidence: 78%
“…The variables of the suggested models indicated that at the maximum and minimum levels of health risk, compared with the average levels, the "safety efficiency" was more significant on "safety view". The results confirmed the acceptability of the suggested and tested model [28].…”
Section: Selection Of the Right Modelsupporting
confidence: 78%
“…At the same time, the stability and validity of the developed approaches are further proved by sensitivity investigation and comparison with existing approaches. It is very meaningful for the proposed methods to be extended in other fuzzy environments [51][52][53][54][55][56][57], uncertain MAGDM problems [58][59][60][61][62][63][64] and risk assessment [65][66][67][68], etc.…”
Section: Discussionmentioning
confidence: 99%
“…In general, in implementing FMEA or EFMEA, three categories are most often considered: severity (S), occurrence (O), and detection (D); they are generally evaluated on a numeric scale of 1 to 10 (Kardos, Lahuta & Hudakova 2021). At the same time, according to the literature, depending on the needs, 9-, 7-, 5-and 3-point scales can also be used (Rahim et al 2021, Wiśniewska 2022. The severity rating ranks the importance of a risk to end-user requirements.…”
Section: Efmea Methods and Its Applicationmentioning
confidence: 99%